Pandemic Covid-19 Preparednes Plan in the Workplace: a Case Study in Mining Company - Henry Ekazandri Iskan; Fatma Lestari (Universitas Negeri Makassar, 2022)
COVID-19 Pandemic preparedness plans in mining companies are very important, so standards are needed as valuable input for all mining companies to make continuous improvements. preparedness plans, so that mining companies do not have to stop operating due to the impact of the COVID-19 pandemic. This study aims for a COVID-19 pandemic preparedness plan in mining companies. The methodology used in this study was to compare mining companies' COVID-19 preparedness plans with ISO/PAS 45005:2020 Standard General guidelines for working safely during the COVID-19 pandemic. The results The results suggest several elements for COVID-19 pandemic preparedness including leadership, risk management. , case management, health protocols, 3Ts (tracing, testing and treatment), emergency management, and case investigations have been identified as key elements for inclusion. The scoring system can be based on the level of implementation of each element. In conclusion, to be better prepared for future pandemics, several strategies have been identified to better manage the pandemic including worker and community participation, worker and public led crisis communication and the RCCE strategy.